2014
DOI: 10.1016/j.jmb.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into the Interaction between Pyk2 and Paxillin LD Motifs

Abstract: Proline-rich tyrosine kinase 2 (Pyk2) is a member of the focal adhesion kinase (FAK) subfamily of cytoplasmic tyrosine kinases. The C-terminal Pyk2 focal adhesion-targeting (Pyk2-FAT) domain binds to paxillin, an adhesion molecule. Paxillin has five leucine-aspartate (LD) motifs (LD1–LD5). Here, we show that the second LD motif of paxillin, LD2, interacts with Pyk2-FAT, similar to the known Pyk2-FAT/LD4 interaction. Both LD motifs can target two ligand-binding sites on Pyk2-FAT. Interestingly, they also share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 69 publications
4
34
2
Order By: Relevance
“…The FAT domain of human Pyk2 (residues 871–1005) was expressed as an N-terminal His-tag fusion in Escherichia coli cells and purified as described. 36 The Pyk2-FAT protein concentration was measured using a standard Coomassie (Bradford) protein assay. The final protein buffer used for all NMR experiments, biochemical studies, and X-ray crystallization was 20 mM MES, pH 6.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAT domain of human Pyk2 (residues 871–1005) was expressed as an N-terminal His-tag fusion in Escherichia coli cells and purified as described. 36 The Pyk2-FAT protein concentration was measured using a standard Coomassie (Bradford) protein assay. The final protein buffer used for all NMR experiments, biochemical studies, and X-ray crystallization was 20 mM MES, pH 6.2.…”
Section: Methodsmentioning
confidence: 99%
“…Leupaxin derived peptides leupaxin-LD1 (human leupaxin, residues 1–20), leupaxin-LD3 (human leupaxin, residues 36–56), leupaxin-LD4 (human leupaxin, residues 86–104), and leupaxin-LD5 (human leupaxin, residues 125–150) were chemically synthesized and purified by high-pressure liquid chromatography (HPLC) at the Hartwell Center of Bioinformatics and Biotechnology of St. Jude Children’s Research Hospital. The length of the leupaxin-LD1, leupaxin-LD3, leupaxin-LD4, and leupaxin-LD5 peptides used was based on our previous paxillin binding studies with Pyk2, 36 FAK, 27 and GIT1. 42 All peptide stocks were prepared at a concentration of 5 mM in 20 mM MES, pH 6.2.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the FAK and Pyk2 FAT domains share 57% sequence identity, form the same 3D structure and bind paxillin LD motifs in the same way (Fig. 5C) (Alam et al, 2014;Hoellerer et al, 2003;Lulo et al, 2009;Vanarotti et al, 2014).…”
Section: Nuclear Pyk2mentioning
confidence: 96%
“…Paxillin is a multidomain adaptor protein that binds to both FAK and PYK2, as well as numerous other FA proteins (e.g., GIT-1, vinculin, and actopaxin) (Turner, 2000). Studies characterizing these protein-protein interactions at the structural level have identified highly conserved four-helix bundled regions, or so called paxillin-binding subdomains, which specifically engage the paxillin N-terminal leucine-rich domains (Brown et al, 1998;Arold et al, 2002;Vanarotti et al, 2014). Paxillin, together with Src and FAK, recruit other proteins to the cell's leading edge where actin filaments coalesce around integrins (cellular "anchors") to provide mechanical forces needed to pull the cell forward.…”
Section: Introductionmentioning
confidence: 99%